1997
DOI: 10.1097/00005650-199706000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Care Reforms on Job Satisfaction and Voluntary Turnover Among Hospital-Based Nurses

Abstract: The authors conclude that although many aspects of job satisfaction are diminished, some factors predicting low satisfaction and turnover may be amenable to change by hospital administrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 9 publications
8
95
2
2
Order By: Relevance
“…The present study had three limitations. First, our questionnaire did not include socioeconomic status and psychological factors related to turnover which were suggested by previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , that is, parental or children care demands, salary level, social support, job demand, and job discretion. Secondly, we were unable to collect the reasons for the turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study had three limitations. First, our questionnaire did not include socioeconomic status and psychological factors related to turnover which were suggested by previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , that is, parental or children care demands, salary level, social support, job demand, and job discretion. Secondly, we were unable to collect the reasons for the turnover.…”
Section: Discussionmentioning
confidence: 99%
“…It can cause decreases in numbers of high-skilled nurses and has an adverse impact on the nursing department, the hospital environment, and the quality of care in medical institutions 1,2) , as well as incurring high costs 3) . Many studies have explored the factors affecting nurses' turnover and their intention of leaving [1][2][3][4][5][6][7][8][9][10][11][12] . They have indicated that the factors affecting intention of leaving were low job satisfaction, inadequacy of staffing, poor salary and welfare, high job stress, low group cohesion, weak leadership by superiors, and work schedule.…”
mentioning
confidence: 99%
“…Indeed, evidence to date suggests that reengineering creates considerable organizational turmoil and employee dissatisfaction that is costly and detrimental to patients. 13 We have demonstrated in other research that the organization of hospital resources, net of actual staffing differences, is an important and underrated factor in explaining variations in hospital outcomes. 14 …”
Section: Methodsmentioning
confidence: 87%
“…Ainsi, un environnement de travail adéquat a le potentiel de réduire le taux de roulement et de burnout des infirmières et d'améliorer la satisfaction des patients par rapport à leurs soins (Vahey et al, 2004). Par contre, un environnement de travail déficient affecte négativement la satisfaction des infirmières et augmente le roulement de celles-ci, entraînant par voie de conséquence des coûts organisationnels accrus (Davidson et al, 1997 ;Irvine et Evans, 1995 ;Lake, 1998 ;Levek et Jones, 1996).…”
Section: Système Modulaire Et D'équipeunclassified